Secret identity - Van Draanen, Wendelin; Biggs, Brian (New York Knopf Distributed by Random House, 2004)
Fifth-grader Nolan Byrd, tired of being called names by the class bully, has a secret identity--Shredderman!
460L
84158
Keywords: Heroes -- Juvenile fiction; Teasing -- Juvenile fiction; Bullying -- Juvenile fiction; Schools -- Juvenile fiction